Analisis Struktur Dan Kinerja Pasar Gabah Di Desa Daya Utama Kecamatan Muara Padang Kabupaten Banyuasin - Puri Pratami Ardina Ningrum; Zaenal Arifin; Rahmat Kurniawan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The purpose of this study is to determine the structure of the grain market and to analyze the performance of the grain market. This study was conducted in Daya Utama Village, Muara Padang District, Banyuasin Regency, South Sumatra Province, from May to July 2025. The research method used was a survey method. Samples were drawn using a simple random method of 30 farmers, using snowball sampling of 3 rice millers and 5 rice collectors. The data analysis methods were 1) to answer the first objective of market share analysis, Concentration Ratio (CR4) and Hirschman-Herfindahl Index (IHH); 2) to answer the second objective of marketing margins and price shares. The results show that the grain market structure in the village is a perfectly competitive market with a CR4 value of 0.181. At the marketing agency level, the market structure tends toward an oligopoly with a CR4 value of 0.609 and a Herfindahl-Hirschman Index (HHI) value of 0.08063. The performance of the grain market in the village in marketing channel I at the collector level is classified as efficient with a marketing margin of 1.72%, at the rice milling level of 124.14%, and in marketing channel II with a marketing margin of 124.14%, indicating that the marketing margin is inefficient. The price share received by farmers in marketing channel I is 45% and in marketing channel II is 44%, which is also considered inefficient.